Urban planning impact on summer human thermal comfort in Doha, Qatar - Shikha, Patel (2024)
Urbanization entails extensive construction and substantial land use alterations, converting natural areas into residential, commercial, mixed-use and industrial. These alterations disrupt the land surface energy, impacting the land surface temperatures (LSTs). Elevated LSTs affect the thermal comfort of urban residents exerting pressure on the environment and ecosystems. This study investigates the repercussions of elevated LST on human thermal comfort, focusing on Doha municipality in Qatar for 2002–2003, 2013, and 2022, with a specific focus on summer temperatures. Utilizing remote sensing and Geographical Information Systems (GIS), we conducted an in-depth investigation, employing Landsat data along and GIS tools to create land use maps and LST pattern maps and establish a correlation between land use and LST. The findings reveal a notable increase in the built-up area of Doha municipality, predominantly at the expense of desert land and water bodies. The LST increases consistently by 0.65 °C annually, shifting human thermal comfort from "moderate" to "heat stress" from 2002 to 2013 and 2023 in all neighborhoods of Doha. Our comparison of LST between different urban areas indicates lower temperatures near water bodies and suburban developments and higher temperatures in downtown areas. Suburban developments exhibit a favourable impact in desert areas compared to compact developments. Our methodology of combining LST from remote sensing data with thermal comfort indices for more comprehensive and accurate estimation of outdoor thermal comfort can be applied in various geographies.